New scenarios for the university development strategy in the international educational space - Mamedov, Agamali K. (2021)
The objective of this research was to show how various approaches to understanding the role, place, and mission of the university have been transformed in the historical retrospective and modern society. The methodological basis of the study is classical and modern works of Russian and foreign scientists and specialists, the methods of theoretical generalization and analysis, method of systematization, interdisciplinary and comparative analysis of sociological, philosophical, cultural, and economic works in the field of higher education, and expert assessments and analysis of the secondary data. As a result, main trends in the development of universities and the socio-cultural determinants of the universities’ transformation were identified. The erosion of traditional university formats and the transition to digital forms of educational and scientific communication were analyzed. Despite the current socio-cultural transformations and the emergence of new models of the university, the university solves its principal tasks of forming a thinking person and trains high-level specialists. However, these processes force the university to revise the traditional structures and principles of existence, as well as to be more attentive to the process of new knowledge and information increment, so as not to fall into the extremes of staying exclusively in education or science.